Detection of Dehalococcoides spp. by peptide nucleic acid fluorescent in situ hybridization - Danko, Anthony S. (2014)
Chlorinated solvents including tetrachloroethene (perchloroethene and trichloroethene), are widely used industrial solvents. Improper use and disposal of these chemicals has led to a widespread contamination. Anaerobic treatment technologies that utilize Dehalococcoides spp. can be an effective tool to remediate these contaminated sites. Therefore, the aim of this study was to develop, optimize and validate peptide nucleic acid (PNA) probes for the detection of Dehalococcoides spp. in both pure and mixed cultures. PNA probes were designed by adapting previously published DNA probes targeting the region of the point mutations described for discriminating between the Dehalococcoides spp. strain CBDB1 and strain 195 lineages. Different fixation, hybridization and washing procedures were tested. The results indicated that the PNA probes hybridized specifically and with a high sensitivity to their corresponding lineages, and that the PNA probes developed during this work can be used in a duplex assay to distinguish between strain CBDB1 and strain 195 lineages, even in complex mixed cultures. This work demonstrates the effectiveness of using PNA fluorescence in situ hybridization to distinguish between two metabolically and genetically distinct Dehalococcoides strains, and they can have strong implications in the monitoring and differentiation of Dehalococcoides populations in laboratory cultures and at contaminated sites.